As políticas públicas de formação continuada de professores/as das escolas do campo: estudo na comunidade do Tracajá numa escola municipal de Parintins-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
This research is the result of two years (2019-2021) of studies in the Master's course in the Graduate Program in Education at the Federal University of Amazonas (PPGE/UFAM), funded in the modality of research scholarship by the Foundation for Research Support in the State of Amazonas (FAPEAM). However, it emerged from personal, academic and professional concerns, as a teacher hired by selection process by SEMED/Parintins, from the participation in the 5th Round of Conversation on Field Education in the Community of São Pedro do Marajó (Uaicurapá River Region), held by the Paulo Freire Forum of Field, Forest and Water Education in Parintiná (FOPINECAF). The following problem emerged: Have the public policies of continuing education for teachers of rural schools met the interests and needs of teachers working in the city of Parintins-AM, specifically in the rural school in the community of Tracajá? It aims to analyze the public policies for continued education for teachers in rural schools in the city of Parintins-AM, specifically in the school of the Tracajá community. And as specific objectives, we unfolded the following: 1) To study the analysis categories: continued formation of teachers; public policies for rural schools; rural education; 2) To investigate how public policies for continued formation of teachers from rural schools are being implemented in the city of Parintins, pointing out possible contradictions and contributions; 3) To examine the formation proposal of the Rural Social Movements for rural schools, considering the continued formation of teachers. The theoretical field is anchored in the studies on Field Education recommended by Arroyo, Caldart and Molina (2011), Arroyo (2007), Molina and Rocha-Antunes (2014), Borges (2015), Silva (2017), Souza (2017) among others, and by studies of authors who address the continuing education of teachers, among them: Gatti, André and Barreto (2009), Imbernón (2010), Libâneo (2015), Silva (2019), Molina and Hage (2015) and others. The methodological path is anchored in the Historical-Dialectical Materialism, involving bibliographic study, document analysis, and application of questionnaires. The locus of the research was the Escola Municipal Luiz Gonzaga, (1) field school from a universe of 118 (one hundred and eighteen) field schools of Parintins, which is located in a settlement area of INCRA. The research included the participation of 1 technician from the Municipal Secretariat of Education (SEMED/PIN), 5 teachers who work in one of the investigated rural schools, the representatives of the rural social movements in Parintins, being the coordinator of FOPINECAF and the coordinator of GRANAV. The main results of the research indicate that the municipality of Parintins has only adhered in recent years policies, programs and projects of continuing education of the federal government developed in agreements with public universities, state and municipal departments of education such as: Active School, Pronera, Gestar, Pro - Literacy, PNAIC and School of Land, however show that such training is still insufficient, most distant from the reality and specificities of the field, do not always contribute and meet the needs of teachers who work in rural schools.
Public policies for continuous teacher training in rural schools: Study in the Tracajá community, in a municipal school in Parintins-AM
Keywords: Educação rural - Parintins (AM); Professores de educação rural - Formação - Parintins (AM); CIENCIAS HUMANAS; Políticas públicas educacionais .; Educação do Campo; Formação continuada de professores/as; Parintins; Amazônia